Numerical and Experimental Study on Energy Performance of Photovoltaic-Heat Pipe Solar Collector in Northern China - Hongbing Chen; Xilin Chen; Sai Chu; Lei Zhang; Yaxuan Xiong (International Journal of Photoenergy)
Several studies have found that the decrease of photovoltaic (PV) cell temperature would increase the solar-to-electricity conversion efficiency. Water type PV/thermal (PV/T) system was a good choice but it could become freezing in cold areas of Northern China. This paper proposed a simple combination of common-used PV panel and heat pipe, called PV-heat pipe (PV-HP) solar collector, for both electrical and thermal energy generation. A simplified one-dimensional steady state model was developed to study the electrical and thermal performance of the PV-HP solar collector under different solar radiations, water flow rates, and water temperatures at the inlet of manifold. A testing rig was conducted to verify the model and the testing data matched very well with the simulation values. The results indicated that the thermal efficiency could be minus in the afternoon. The thermal and electrical efficiencies decreased linearly as the inlet water temperature and water flow rate increased. The thermal efficiency increased while the electrical efficiency decreased linearly as the solar radiation increased.